Extensive myocardial calcifications: a systematic literature review of a rare pathological phenomenon - Sozzi, Fabiola B.; Gnan, Eleonora; Faggiano, Andrea; Giangiacomi, Francesco; Iacuzio, Laura; Canetta, Ciro; Santangelo, Gloria; Pisaniello, Marco; Eker, Armand; Carugo, Stefano (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Myocardial calcifications (MC) represent a relatively rare pathological process, which may accompany different cardiovascular conditions and can be broadly categorized as dystrophic or metastatic. Myocardial infarction (MI) has been traditionally regarded as the main cause of MC overall; however, no updated comprehensive data on the relative incidence of different forms of MC is available. The purpose of this systematic review of the literature is to analyze the currently available evidence on MC in terms of pathophysiology, diagnosis, and clinical presentation.Methods and Results: A total of 241 studies including a total of 368 patients affected by extensive MC were included in the final review. The majority of patients (69.8%) presented with dystrophic MC. Endomyocardial fibrosis (EMF) represents the single most common etiology of MC (24.2%), while sepsis/acute systemic inflammatory syndrome (SIRS) and chronic kidney disease were identified as the second and third most common causes respectively. The relative incidence of etiologies also varies across the years, with MI being more represented before 1990, and sepsis/SIRS becoming the single most common cause of MC after 1990. Multimodality imaging was used in the work-up of MC in 42.7% of cases. The most commonly employed imaging modality overall was echocardiography (51.9%), while after 1990 computed tomography scan became the most widely used tool (70.1%).The present systematic review provides new insights into the pathophysiology of MC. Previously thought to be mainly a consequence of ischemic heart disease, our data indicate that other diseases, namely EMF and sepsis/SIRS, are indeed the main conditions associated with MC. The importance of multimodality imaging in the work-up of MC is also highlighted.